Assessing Software Engineering Students' Analytical Skills in the Era of Generative AI - Olga Petrovska (Proceedings of the 9th Conference on Computing Education Practice, 2025)
This poster showcases an assessment designed to develop and evaluate software engineering students’ code analysis skills. We demonstrate how students approached code analysis tasks when given multiple code samples created by a human and various AI tools.